The Existence and Power of Fisherwomen in Morodemak and Purworejo Villages: Against Violence, Bureaucracy & Biased of Religious Interpretation - Pratiwi, Andi Misbahul; Boangmanalu, Abby Gina (Yayasan Jurnal Perempuan, 2017)
This research was conducted in Morodemak and Purworejo Villages, Demak District, Central Java Province, Indonesia, by focusing on problems faced by fisherwomen—those who go out to sea as well as those who process fishing catch—and the activism of Puspita Bahari (fisherwomen organization in Demak). This research aims to show that women have contributed to the economic progress of coastal communities. Additionally, this research became a personal project as the researchers had the opportunity to directly observe the activities of fisherwomen who go out to sea. Furthermore, in the research process, the researchers participated in the advocacy process to help fisherwomen gain recognition for the work they do. By using Naila Kabeer’s gender analysis, this research found that the complexity of the problems faced by fisherwomen are truly layered and involve the family, community and market. Division of labor, biased bureaucracy and domestic violence are the three main topics studied in this paper. It’s urgent to recognize fisherwomen, as this recognition would be the first step that must be taken in order to improve the lives of fisherwomen.